Strengthening the Marketing of Pediatric Cardiac Surgery Services to Support the Transformation of Health Services in Indonesia - Gunardi, Felicia; Oktamianti, Puput (Journal of Indonesian Health Policy and Administration, 2023)
This study aims to determine the marketing strategy 7P carried out by cardiac surgery services in Indonesia and to identify actionable policy recommendations. This study is observational descriptive research. Data were collected from Cardiothoracic and Vascular surgeons and hospital websites with cardiac surgery services. Through the marketing analysis approach of 7P, this study identifies problems and policy recommendations that can be alternative solutions. The price of the service is high, but most of the patients used BPJS, and it is found that the hospital rate is higher than BPJS claims. The actionable recommendation to respond to it is that the hospital should provide the costing and financial analysis that generate the hospital rate to BPJS revise the BPJS's claims. It can only be done if hospitals from many regions produce similar rates or slight variations. Jabodetabek still dominates as the region (place) with the most cardiovascular surgery services in Indonesia, with 29 of 35 hospitals. Actionable recommendations to respond to this issue include ensuring data on demand for cardiac surgery services from various regions and encouraging the government through specialist expert associations and legislation to provide cardiovascular surgery services in various regions - outside Jabodetabek. Regarding the specialist (people), the government must provide scholarships for doctors to take BTKV specialists, especially those who can perform pediatric ones.